Checklist of Cuban rudist taxa - Reinaldo Rojas; Manuel Iturralde-Vinent (Revista Mexicana de Ciencias Geológicas)
In the shallow-water Cretaceous deposits of Cuba, Aptian to Maastrichtian rudist faunas have been found within two main general tectonic setting: the Bahamian carbonate platform and the Cretaceous volcanic arc, in limestone lenses and small carbonate platforms… in order to continue, download the full paper in PDF.